Tratamiento de la terminología referente a la indumentaria provenzal de Mirèio en francés y español - Jiménez-Cervantes Arnao, María del Mar (Anales de Filología Francesa, 2010)
Mistral’s work Mirèio is a portrait of rural life in Provence in the 19th century. In this paper we are analysing clothing terminology in the first French and Spanish translations of this work, carried out by Mistral and Barallat y Falguera, with the aim of contrasting the diversity in local terms as they appear in these two languages.